Synergistic Antimicrobial Effects of Phage vB_AbaSi_W9 and Antibiotics against Acinetobacter baumannii Infection - Yoon-Jung Choi; Shukho Kim; Minsang Shin; Jungmin Kim (MDPI AG, 2024)
Acinetobacter baumannii is a challenging multidrug-resistant pathogen in healthcare. Phage vB_AbaSi_W9 (GenBank: PP146379.1), identified in our previous study, shows lytic activity against 26 (89.66%) of 29 carbapenem-resistant Acinetobacter baumannii (CRAB) strains with various sequence types (STs). It is a promising candidate for CRAB treatment; however, its lytic efficiency is insufficient for complete bacterial lysis. Therefore, this study aimed to investigate the clinical utility of the phage vB_AbaSi_W9 by identifying antimicrobial agents that show synergistic effects when combined with it. The A. baumannii ATCC17978 strain was used as the host for the phage vB_AbaSi_W9. Adsorption and one-step growth assays of the phage vB_AbaSi_W9 were performed at MOIs of 0.001 and 0.01, respectively. Four clinical strains of CRAB belonging to different sequence types, KBN10P04948 (ST191), LIS2013230 (ST208), KBN10P05982 (ST369), and KBN10P05231 (ST451), were used to investigate phage-antibiotic synergy. Five antibiotics were tested at the following concentration: meropenem (0.25-512 µg/mL); colistin, tigecycline, and rifampicin (0.25-256 µg/mL); and ampicillin/sulbactam (0.25/0.125-512/256 µg/mL). The in vitro synergistic effect of the phage and rifampicin was verified through an in vivo mouse infection model. Phage vB_AbaSi_W9 demonstrated 90% adsorption to host cells in 1 min, a 20 min latent period, and a burst size of 114 PFU/cell. Experiments combining phage vB_AbaSi_W9 with antibiotics demonstrated a pronounced synergistic effect against clinical strains when used with tigecycline and rifampicin. In a mouse model infected with CRAB KBN10P04948 (ST191), the group treated with rifampicin (100 μg/mL) and phage vB_AbaSi_W9 (MOI 1) achieved a 100% survival rate-a significant improvement over the phage-only treatment (8.3% survival rate) or antibiotic-only treatment (25% survival rate) groups. The bacteriophage vB_AbaSi_W9 demonstrated excellent synergy against CRAB strains when combined with tigecycline and rifampicin, suggesting potential candidates for phage-antibiotic combination therapy in treating CRAB infections.